Sítios anatômicos incomuns e apresentações anatomopatológicas pouco frequentes do linfoma em cães - Mazaro, Renata Dalcol (2018)
This dissertation involved the retrospective study of different anatomopathological types of lymphoma that were diagnosed in the Laboratório de Patologia Veterinária of the Universidade Federal de Santa Maria between 1965 and 2017. Of a total of 100 dogs with lymphoma, 16 (16% of cases), the macroscopic and/or histopathological findings allowed us to admit, from the international literature, that they were cases not traditionally described: follicular lymphoma, (5/100 [5%]), peripheral T-cell lymphoma, nonspecific (2/100 [2%]), angiocentric lymphoma (2/100 [2%]), intravascular large T-cell lymphoma (2/100 [2%]), lymphomatoid granulomatosis (1/100 [1%]), anaplastic large cell lymphoma (1/100 [1%]), hepatosplenic T-cell lymphoma (1/100 [1%]) and small lymphocytic lymphoma – intermediate type (1/100 [1%]).Further study of these cases was the objective of this dissertation, so that with the results expressed herein, veterinary pathologists will recognize such “atypical lymphomas". This study resulted in four scientific papers (two articles and two case reports) that are part of this dissertation: 1) Uncommon anatomical sites and non-traditional anatomopathological presentations of lymphoma in dogs, 2) Epidemiological, clinical and pathological aspects of follicular lymphoma in dogs, 3) Intravascular large T-cell lymphoma in two dogs, and 4) Pagetoid reticulosis in a dog.